The Influence Of Discounts And Live Streaming On Implusive Purchasing Decisions For Fashion Products On TikTok Shop In Gumay Talang District - Liga Elsita; Delvina Yulanda; Heri Fitriadi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The objective of this reasearch is to examine the influence of discounts and live streaming on impulsive purchasing decisions for fashion products at TikTok Shop in Gumay Talang District. The method applied in this analysis is a descriptive quantitative method. Sampling used purposive sampling, which involved 96 respondents. The data analysis approach adopted is multiple linear regression, assisted by SPSS. The study findings show that discounts and live streaming have a positive and significant effect on impulsive purchasing decisions. These findings can help marketers/sellers in developing increasingly effective marketing strategies through discounts and live streaming.